A bibliometric of financial technology QR Code and QRIS research - Vella, Anisyah (2024)
This study aims to determine the development of the use of technology-based financial transactions or Fintech, especially in QR codes and QRIS Fintech. This research discusses parameters related to many previous studies related to financial technology QR codes and QRIS. The bibliometric method identifies and analyzes publication patterns, the most productive authors, the journals that publish the most related articles, and research trends related to Fintech (QR Code and QRIS). Data collection was conducted in September 2023 on the Scopus database and data analysis using Rstudio, Biblioshiny, and VOSviewer applications. The results of this bibliometric analysis provide important insights into the development of research related to Fintech (QR Code and QRIS). It was found that the discussion of the two themes was still minimally researched as seen from the results of the QR Code theme 16 published documents and QRIS 7 published documents.